Teacher ratings of academic achievement of children between 6 and 12 years old from intact and non-intact families - Lephodisa S. Molepo; Levison Maunganidze; Pilot Mudhovozi; Tholene Sodi (Perspectives in Education, 2010)
We investigated teacher ratings of the impact of parental divorce on academic achievement of children between 6 and 12 years old up to 12 months after their parents divorced. A purposive sample of 120 children attending four different primary schools in a small South African town took part in the study. One third (n 40) of the children had experienced parental divorce (male 14, female 26) while two thirds had not. Teachers rated participating children in their class on academic performance on the Conners rating scale ranging from 0 to 3. In addition, teachers ob tained the average term score of each of the participating children in key academic areas, which were converted to the Conners scale for classification. Chi square tests were used to analyse the data. Results showed that the academic performance of children from non intact families within the age range of 6 9 was inferior to that of their counterparts from intact families suggesting that the experience of parental divorcee had a negative impact on children’s academic achievement. It is recommended that future research compare teacher ratings with children’s ratings on standardised tests.